African human capital and labour report. (KR Publishing and Knowledge Resources, 2018)
KR's HUMAN CAPITAL AND LABOUR RESEARCH provides in-depth and comprehensive data of the latest human capital and labour trends and developments in various African countries. Each country report will provide you with a better understanding and knowledge of the context of human capital and labour in terms of: - Labour market efficiency - Employment levels and trends - Unemployment and job creation - Wage and salary trends - Training and skills development - Skills shortages - Industrial relations - Education - Inter-cultural challenges - Economic indicators - Standards of living - Healthcare - Expatriates, immigrants and diaspora - Human resources profession and more. In addition, the research sets these developments in context and explains their significance. Data is benchmarked against South Africa and Nigeria to provide context and perspective. This enables you to make better strategic decisions for your organisation. Our integrated country reports are a must to read if you want to analyse labour market trends and identify human capital business risks!